Bioresources and bioprocessing - Hua dong li gong da xue. Sheng wu fan ying qi gong cheng guo jia zhong dian shi yan shi (Springer-Verlag, GmbH, 2014)
Bioresources and Bioprocessing (BRBP) aims at providing an international academic platform for exchanging views on and promoting research to support bioresource development, processing and utilization in a sustainable manner. As an application-oriented research journal, BRBP covers not only the application and management of bioresource technology but also the design and development of bioprocesses that will lead to new and sustainable production processes.
Keywords: Biotechnology : Periodicals; Biochemical engineering : Periodicals; Biomedical Engineering; Biodegradation, Environmental; Biochemical Phenomena; Biotechnology; Biochemical engineering